Experimental study on the impact load characteristics of a single-row pile dam against debris flow - Hao Sun; Zhuang Wang; Yong You; Wanyu Zhao; Jinfeng Liu; Dongwei Wang (Geomatics, Natural Hazards & Risk)
A single-row pile dam is a type of rigid debris flow barrier structure. In order to reveal the mutual interaction effects between debris flow and a single-row pile dam and the distribution law of debris flow impact forces, an analysis of the correlation between debris flow density, characteristic particle size, and relative pile spacing (the ratio of pile gap size to debris flow characteristic particle diameter) and debris flow impact forces was conducted to obtain dimensionless parameters related to debris flow impact force and climbing height. These parameters were verified through flume model experiments to provide theoretical support for the engineering design of single-row pile dams. The results show that the impact force of the debris flow on the pile dam is mainly affected by the flow velocity, debris flow density, and relative pile spacing. The dimensionless parameters are introduced, and the semi-empirical expression of the impact load coefficient is established. The impact pressure coefficient of debris flow is classified into two categories, and the calculation model of impact load of a single-row pile dam is constructed. The research results can provide a theoretical basis and technical parameters for designing a single-row pile dam.